PENINGKATAN PENGETAHUAN IBU BALITA TENTANG TANAMAN OBAT KELUARGA SEBAGAI UPAYA MELESTARIKAN BUDAYA LOKAL - Kasmara, Dwi Pratiwi; Yusman, Reni; Khairunnisa, Siti; Khairani, Khairani; Hasibuan, Idayani; Pariyanti, Sri; Kasih, Lisna (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2024)
Family medicinal plants have long been an integral part of traditional healthcare practices across various cultures worldwide. Communities have relied on these plants as a source of remedies for mild health issues and as environmentally-friendly alternatives to healthcare. The use of family medicinal plants is often rooted in generational knowledge that has proven effective in alleviating symptoms of illnesses. This research aims to improve the knowledge of mothers with toddlers regarding family medicinal plants as an effort to preserve local culture in Basilam Bukit Lambasa. Through education and training methods, it is hoped that the local community can utilize family medicinal plants as an alternative form of treatment while preserving their cultural heritage. Pre-Education Results: It was found that 68% of mothers with toddlers had basic knowledge about family medicinal plants, but only 20% of them incorporated this knowledge into their daily lives. Post-Education Results: After participating in the training program, 85% of mothers with toddlers demonstrated an increased understanding of family medicinal plants, and 50% of them began to utilize these plants in their daily lives.